2018
DOI: 10.12688/hrbopenres.12796.1
|View full text |Cite
|
Sign up to set email alerts
|

The use of eHealth to promote physical activity in patients with mental health conditions: a systematic review

Abstract: Background: Achieving adequate amounts of physical activity (PA) confers important physical and mental health benefits. Despite this, individuals with mental health conditions often do not meet recommended levels of PA. eHealth, the delivery of health information through internet and mobile technologies, is an emerging concept in healthcare which presents opportunities to improve PA in people with mental conditions. The aim of this systematic review is to explore if eHealth interventions increase PA levels amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…One of the well-known healthcare practices is eHealth. A study carried out by [31] discussed the use of eHealth to promote physical activities in patients with mental health conditions. Physical activities can improve mood and sleep, reduce stress as well as to strengthen self-esteem.…”
Section: B Anxiety Among Freshman Studentsmentioning
confidence: 99%
“…One of the well-known healthcare practices is eHealth. A study carried out by [31] discussed the use of eHealth to promote physical activities in patients with mental health conditions. Physical activities can improve mood and sleep, reduce stress as well as to strengthen self-esteem.…”
Section: B Anxiety Among Freshman Studentsmentioning
confidence: 99%
“…Facebook groups have previously been used effectively to deliver behavioural change interventions in both the general population and in people with serious mental illness 27 28. A recent review found that eHealth technologies including social media platforms such as Facebook can increase PA levels and may have beneficial effects on mental health outcomes in patients with mental illness 29. The reach and popularity of social networking sites such as Facebook may therefore offer highly scalable and cost-effective opportunities for engaging first responders in PA-focused lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%